La peur des reptiles (récits de voyage, xvie-xviiie siècle) - Jean-Paul Duviols (Caravelle)
The first European discoverers of the New World wrote stories full of awe and amazement which favoured descriptions of «wild» indigenous populations, and were replaced by other accounts focused on nature, thus contributing to develop America’s exotic vision. In the vernacular wildlife, reptiles became an outstanding subject: this study presents fragments of illustrated travel stories (16th-18th centuries), either picturesque o more seriously documented, aiming to satisfy European curiosity for American snakes.